Psoralen-mediated regulation of osteogenic differentiation of periodontal ligament stem cells: involvement of the mTOR pathway - Wang, Yujia; Zhang, Hongbo; Yu, Jie; Jing, Jin; Fu, Zhaojiang; Hao, Yuanping; Huang, Qihang; Ma, Ruibin; Xu, Yingjie; Wu, Yingtao (Frontiers in Cell and Developmental Biology, 2025)
BackgroundChronic periodontitis is a prevalent inflammatory and destructive oral disease, and its primary treatment is to control the development of inflammation and promote the regeneration of periodontal tissue. Psoralen (Pso) has been shown to promote the osteogenic differentiation of periodontal ligament stem cells (PDLSCs), suggesting its potential as a therapeutic agent for osteogenic regeneration.MethodsNetwork pharmacology and transcriptomic sequencing were exploited to screen target genes of Pso in PDLSCs, lentiviruses were employed to interfere with the target gene, and RT-qPCR was conducted to assess the expression levels of osteogenesis-related factors. Pso-loaded mesoporous polydopamine (MPDA-Pso) nanoparticles were constructed and evaluated in vitro, and in vivo osteogenesis was assessed in rats with alveolar bone defects.ResultsNetwork pharmacology analysis revealed that the mammalian target of rapamycin (mTOR) was a potential target of Pso, and Pso significantly modulated the expression levels of mTOR in PDLSCs and markedly enhanced osteogenic differentiation. However, Pso did not significantly alter osteogenesis-related genes in PDLSCs after mTOR-inhibitor treatment. We also confirmed that MPDA-Pso nanoparticles promoted the expression of osteogenesis-related genes in PDLSCs; and compared with the control group, observed that the mass of new bone was augmented in the MPDA-Pso group.ConclusionPso was shown to promote the osteogenic differentiation of PDLSCs, and we postulate that this differentiation was facilitated in the LPS-induced inflammatory microenvironment via inhibition of the autophagy-related mTOR-signaling pathway. Additionally, the MPDA-Pso nanoparticles we developed promoted osteogenesis.